Species and embryo genome origin affect lipid droplets in preimplantation embryos - Lipinska, Paulina; Pawlak, Piotr; Warzych, Ewelina (Frontiers in Cell and Developmental Biology, 2023)
Mammalian embryo development is affected by multiple metabolism processes, among which energy metabolism seems to be crucial. Therefore the ability and the scale of lipids storage in different preimplantation stages might affect embryos quality. The aim of the present studies was to show a complex characterization of lipid droplets (LD) during subsequent embryo developmental stages. It was performed on two species (bovine and porcine) as well as on embryos with different embryo origin [after in vitro fertilization (IVF) and after parthenogenetic activation (PA)]. Embryos after IVF/PA were collected at precise time points of development at the following stages: zygote, 2-cell, 4-cell, 8/16-cell, morula, early blastocyst, expanded blastocyst. LD were stained with BODIPY 493/503 dye, embryos were visualized under a confocal microscope and images were analyzed with the ImageJ Fiji software. The following parameters were analyzed: lipid content, LD number, LD size and LD area within the total embryo. The most important results show that lipid parameters in the IVF vs PA bovine embryos differ at the most crucial moments of embryonic development (zygote, 8-16-cell, blastocyst), indicating possible dysregulations of lipid metabolism in PA embryos. When bovine vs porcine species are compared, we observe higher lipid content around EGA stage and lower lipid content at the blastocyst stage for bovine embryos, which indicates different demand for energy depending on the species. We conclude that lipid droplets parameters significantly differ among developmental stages and between species but also can be affected by the genome origin.